Lithium decoration of boron-doped hybrid fullerenes and nanotubes as a novel 3D architecture for enhanced hydrogen storage: A DFT study. (28th January 2019) - Bi, Lan; Yin, Jie; Huang, Xin; Ren, Shanling; Yan, Gang; Wu, Qiang; Wang, Yunhui; Yang, Zhihong
Abstract: A three dimensional (3D) dumbbell-like nanostructure composed by interconnected fullerenes and nanotubes with Lithium decoration and boron-doping (37Li@C139 B31 ) has been proposed in virtue of density functional theory (DFT) and first-principles molecular dynamics (MD) simulations which shows excellent geometric and thermal stability. First-principles calculations are performed to investigate the hydrogen adsorption onto the 37Li@C139 B31 . The results indicate that B substitution can improve the metal binding and the average binding energy of 37 adsorbed Li atoms on the C139 B31 (2.79 eV) is higher than the cohesive energy of bulk Li (1.63 eV) suppressing the clustering. Meanwhile, the H2 storage gravimetric density of 178H2 @37Li@C139 B31 reaches up to 15.9 wt% higher than the year 2020 target from the US department of energy (DOE). The average adsorption energy of H2 molecules falls in a desirable range of 0.18–0.27 eV. Moreover, grand canonical ensemble Monte Carlo (GCMC) simulations reveal that at room temperature the hydrogen gravimetric density (HGD) adsorbed on 37Li@C139 B31 reaches up to 11.6 wt% at 100 bars higher than the DOE 2020 target. Our multiscale simulations indicate that our proposed nanostructure provides a promising medium for hydrogen storage. Graphical abstract: Calculated H2 adsorption isotherms by GCMC in nLi@C170-m Bm complex as a function of the pressure at T = 298 K. The inset: the side view of optimized 178 H2 @37Li@C139 B31 complex by a DFT study. Gray indicates C; pink, B; purple, Li; white, H. Highlights: A dumbbell-like structure by attaching carbon nanotube to fullerenes is modelled. Both Li decoration and B substitution improve hydrogen adsorption. The average binding energy of adsorbed Li atoms (2.79 eV) avoids metal clustering. High hydrogen storage capacity is attained from DFT (15.9 wt%). Hydrogen gravimetric density reaches 11.6 wt% at 298 K and 100 bars from GCMC.